A distinct double positive IL-17A+/F+ T helper 17 cells induced inflammation leads to IL17 producing neutrophils in Type 1 reaction of leprosy patients. (February 2020) - Saini, Chaman; Srivastava, Rupesh K.; Kumar, Praveen; Ramesh, V.; Sharma, Alpana
Highlights: This study suggests that IL17A + /F + Th cell involved in the immunopathology of T1R. Study correlates neutrophils markers with IL17A and F and reports pathogenesis of T1R. Hierarchical analysis of CXCL5, 6, CCL7, 20, MMP13 and IL17R genes are associated with IL-17A/ F . Abstract: Type 1 reactions (T1R) an inflammatory condition, of local skin patches in 30–40% leprosy patients during the course of MDT. IL-17A and IL-17F play an important role in regulating skin inflammation through neutrophils. In the present study, we have analyzed 18 of each T1R and Non-reactions (NR) patients through flow cytometry and qPCR. Interestingly we found that, CD3 + CD4 + gated IL-17A + IL-17F + cells were significantly high in T1R in both MLSA stimulated PBMCs and skin lesions as compared to NR leprosy patients. Hierarchical clustering analysis of gene expression showed that CXCL6, CXCL5, CCL20, CCL7, MMP13 and IL-17RB expression were significantly associated with IL-17A and IL-17F expression (Spearman r 2  = 0.77 to 0.98), neutrophils and monocyte markers respectively. In this study, the inflammation noted in lesions of T1R is a different phenotype of Th17 which produce double positive IL-17A + IL17F + and also contributes IL-17 producing neutrophils and thus would be useful for monitoring, diagnosis and treatment response before reactions episodes.